Penerapan Ular Tangga Sebagai Media Memperbaiki Tanda & Gejala Risiko Perilaku Kekerasan pada ODGJ di Rumah Sakit Jiwa Palembang - Dini Anggraini; Aprida Manurung; Bangun Dwi Hardika (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
The risk of violent behavior is the result of anger or fear which is a response to feelings of threat, which will show several signs and symptoms such as sharp gaze, stiff body posture, red face and harsh words, so intervention is given using the media using snakes and ladders to improve the signs and symptoms. violence. Aiming to improve the signs and symptoms of violent behavior through modality therapy using the snakes and ladders game, the method used is a case study to explore nursing care to improve the signs and symptoms by observing and pre-test and post-test checklists on clients with violent behavior. The results of the implementation that had been carried out were a decrease in 14 signs and symptoms of violent behavior, in patient I there was a decrease in 4 out of 6 signs and symptoms, in patient II there was a decrease in 7 out of 10 signs and symptoms, in patient III there was a decrease in 3 out of 5 signs and symptoms. , patient IV experienced a decrease in 6 of 9 signs and symptoms, patient V experienced a decrease in 4 of 7 signs and symptoms and patient VI experienced a decrease in 4 of 9 signs and symptoms of violent behavior. So there is an influence on the application of the snakes and ladders game media to improve signs and symptoms in patients with violent behavior.